Mediating Human-Wolves Conflicts Through Dialogue, Joint Fact-Finding and Empowerment - Hansen, Hans Peter; Dethlefsen, Cathrine S.; Fox, Gwen Freya; Jeppesen, Annika Skarðsá (Frontiers in Environmental Science, 2022)
Within a local and national context of escalating conflicts surrounding the management of immigrating wild wolves (Canis lupus) spreading from Germany into Denmark, we invited a group of citizens living in and nearby a Danish wolf territory to participate in an experiment called ‘The Wolf Dialogue Project’. The overall objective of the Wolf Dialogue Project was to explore the possibility of developing a productive alternative to the systematically distorted communication and ‘High conflict’ that characterizes current wolf management, using a critical-utopian dialogue approach guided by Habermasian discourse ethic and a joint fact-finding process, that seeks to empower citizens to take on a shared responsibility for the commons. By purposefully not representing any strategic interests for or against wolves or the existing wolf management regime, the project offered a group of citizens the opportunity to formulate and communicate the problems and concerns they experienced, living in or nearby wolf territory. The project further offered the participating citizens the opportunity to develop counter measures and solutions to their experienced problems, through a facilitated process of social learning and empowerment. The duration of the dialogue project was two and a half years and included a demographic and political cross section of local citizens. Despite difficulties along the way, the outcome of the project was more profound than initially anticipated by the project team. Participants were initially very polarized and some were opposed to the existing wolf management regime as well as governmental agencies, but they began taking on a collective responsibility guided by the common interest of their community, across individual differences. In addition, the process left a significant mark on the new wolf management plan recommended to the government by the Danish Wildlife Council in 2021. Far from all problems and conflicts were solved by the project, and new problems also emerged as a result of the project, but by bringing the commons of the participating citizens into focus, and applying a process of communicative rationality, joint fact finding and the exploration of alternative futures, the project revealed the potential for social and environmental responsibility to emerge from sociopolitical empowerment.